Identification of the Application of Regionalism Architecture in Buildings in the City Hall Corridor Area, Medan - Ulinata (Formosa Journal of Science and Technology, 2023)
Each region has its own regional characteristics, depending on the local culture, climate, and existing technology. Thus, architects from various regions around the world have their own mindsets regarding regionalism theory, so there are several tendencies regarding its embodiment. This study aims to identify the application of regionalism architecture to buildings in the City Hall Road Corridor Area, Medan, by using a descriptive qualitative method obtained from field observation data and then presented descriptively. There are several buildings that apply regionalism architecture in the City Hall corridor area of Medan, namely City Hall, Post Office, Bank Mandiri, Bank Indonesia, and Dharma Deli Hotel, with the concept applied through fulfilling criteria for being responsive to the local climate, socio-culture, political and economic conditions, technological developments, and building identification based on symbols.